O pacifismo institucional cosmopolita kantiano: história, teoria e crítica - Frexeira Junior, George Leite (2021)
This research proposes to critically analyze the theoretical possibilities of cosmopolitanism as a progressive political solution to deal with wars, violations of human rights and instability in international relations, to this end, it investigates the main elements that constitute the Kantian Cosmopolitan Institutional Pacifism, which it seeks, above all, the promotion of political and legal mechanisms that favor a lasting peace among nations. The research hypothesizes that the rhetorical and circumscribed character of any discourse with supposedly unconditional pretensions is considered, since they are committed to a circumspect perspective of reality, thus, paying attention to the conditional character of universalist pacifist topics, it expands the realization of human freedom and dignity, as the different local idiosyncrasies are respected. Kant, with his proposal for perpetual peace, upholds human dignity as a principle of freedom and legal equality between nations, therefore, suggests the construction of a confederation of free States antagonistic to war: a reasonable and desirable proposal, which preserves its actuality in contemporaneity, but which must be understood in the context of ideas. His political pacifism is related to Saint-Pierre and Rousseau, who influenced him in his project of perpetual peace, Bobbio is inserted in the continuity of this Kantian project, when reflecting on the possibilities of democratization of international relations, Habermas, on the other hand, in a way Critics performs a conceptual review of the Kantian project of perpetual peace and considers its readaptation to the present, by suggesting a world republic of States with centrality in supranational institutions that would act to regulate the relationships of individuals. For the political realist Danilo Zolo, it is plausible that the Habermasian discourse on the reconstruction of Kantian cosmopolitanism encounters political, cultural, economic and moral issues, which may consequently result in a utopia in terms of its ethical and legal approach. Which leads us to Perelman, who considers the essentiality of a rhetorical and argumentative rationality as a pluralism of ideas and horizontalization of multiple discourses. Contrary to any radicalization of the Kantian proposal of perpetual peace and the promotion of a univocal conception of reality, we understand that the cosmopolitan topic is a promising theoretical perspective for international relations, as long as it is considered an idea of hope in a permanent political improvement, juridical and moral of humanity.